Civil-military relations in Pakistan: an analysis of Sino-Pakistani ties 2001-2016 - Boni, Filippo (2017)
This thesis assesses the extent of military prerogatives in Pakistan’s domestic politics, by focusing on Sino-Pakistani relations in the post 9/11 period. The study departs from the coup-centric approach largely adopted in the literature on civil-military relations and develops a continuum of civil-military relations which identifies four different intensities of civilian control over the military. Such a scale is deployed to gauge empirically the military’s sway in four decision-making areas: internal security, foreign policy, economic policy and elite recruitment. This structure is used to analyse the three case studies presented in the thesis: 1) the development of the port of Gwadar; 2) the China-Pakistan Economic Corridor; and 3) Sino-Pakistani relations in the Afghan scenario. The empirical chapters are organised around elite interviews conducted during fieldwork in Pakistan and triangulated with primary and secondary sources. From the analysis conducted in the thesis emerges a new pattern of civil-military relations in Pakistan, a situation in which the civilians and the military are sharing power to the benefit of both parties. The military have found it in their interest to exercise power less overtly and to retain control of internal security and foreign policy behind the curtain of a democratic dispensation. The civilians, on their side, have managed to erode military influence in the areas of elite recruitment and economic policy, in their attempts to tackle the energy crisis and to win the 2018 general elections. Such a pattern starts taking shape in the 2008-2013 period, but it becomes more crystallised in the post-2013 time frame. The thesis assesses specifically military prerogatives in the context of Pakistan’s relations with China, but also extends the picture in the final chapter to the wider developments in civil-military relations in Pakistan, in order to provide a comprehensive and solid analysis of the issue under examination.